Pemanfaatan Karbon Aktif dari Limbah Kulit Pisang Kepok (Musa Paradisiaca L) sebagai Elektroda Superkapasitor - Khariezmathika Ester Kapantow; Alfrie Musa Rampengan; Farly Reynol Tumimomor; Heindrich Taunaumang; Sixtus Iwan Umboh (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
In recent years, attention to renewable energy has increased, especially in electrical energy. One of the emerging technologies in supporting electrical energy storage is supercapacitors. This study aims to determine the effect of variations in the concentration of KOH solution on the current and voltage characteristics produced by supercapacitor electrodes made from activated carbon from kepok banana peel waste (Musa Paradisiaca L). By using dehydration method 80°C, carbonization at 400°C, chemical activation with 5M, 6M, and 7M KOH solution, and physical activation at 750°C. The results showed that the concentration of KOH activator from 5M, 6M, to 7M increased the electric voltage to 0.641 V, 1.078 V, and 1.448 V and electric current to 10.3 mA, 11.6 mA, and 28.5 mA, respectively. However, the density and conductivity values showed different patterns, with density values of 1.2446 A/